Directive Speech Acts in Habiburrahman El-Shirazy's Novel Pudarnya Pesona Cleopatra (A Pragmatic Study) - ulum, Ilham Bachrul; Nurchalistiani Budiana; Robert Rizki Yono (Universitas Swadaya Gunung Jati, 2025)
Directive speech acts in the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy, Indonesian Language and Literature Education. Muhadi Setiabudi University Brebes. This study aims to describe the analysis of the types and functions of directive speech acts in the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy using a pragmatic approach according to J.L. Searle's speech act theory. The focus of this study is on the grouping of the speech acts of the characters in the novel that are included in the category of directive speech acts, such as advising, ordering, begging, prohibiting, giving suggestions, and requesting. This research method uses qualitative descriptive, with data analysis techniques in the form of identification, classification, and interpretation of data based on the context of the speech. The results of the study showed 62 data on the types and functions of directive speech acts which were divided into six categories, namely: (1) Advising directives 4 data (2) Commanding directives 12 data (3) Requesting directives 8 data (4) Prohibiting directives 9 data (5) Advising directives 10 data (6) Requesting directives 19 data. The most dominant type of directive speech act found was the requesting directive speech act. This shows that the communication in this novel contains many requests from one character to another, which depict interpersonal relationships and personal conflicts. Thus, the results of this study indicate that directive speech acts play an important role in building the storyline and character characteristics in the novel.